2011
DOI: 10.1590/s0104-66322011000200017
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-liquid equilibrium measurements for the binary system methyl acetate+ethanol at 0.3 and 0.7 MPa

Abstract: -This paper reports experimental data of the isobaric vapor-liquid equilibria (VLE) for the mixture methyl acetate + ethanol at 0.3 and 0.7 MPa, determined using a copper still ebulliometer. The activity coefficients obtained from the experimental data were correlated by using different thermodynamic mathematical models. All the binary systems show a positive consistency when subjected to the point-to-point test of Van Ness. The prediction of VLE data obtained with the UNIFAC and ASOG methods has been verified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Methyl acetate with a purity of > 99.0 % and ethyl acetate with a purity of > 99.9 % have been employed, both from Panreac Quimica S.A., with properties not different from that previously published. , The normal boiling point ( T bp ), density (ρ ii ) and refractive index ( n D ) at 298.15 K of 2-butanol, from Sigma-Aldrich (purity higher than 99.5 %), and their comparison with literature data are presented in Table . These substances were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methyl acetate with a purity of > 99.0 % and ethyl acetate with a purity of > 99.9 % have been employed, both from Panreac Quimica S.A., with properties not different from that previously published. , The normal boiling point ( T bp ), density (ρ ii ) and refractive index ( n D ) at 298.15 K of 2-butanol, from Sigma-Aldrich (purity higher than 99.5 %), and their comparison with literature data are presented in Table . These substances were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…After that, samples from both the liquid and vapor phases were extracted. These were analyzed as in previous works. A calibration curve density vs composition previously prepared allowed the calculation of the composition of both phases. Table shows the data corresponding to the ester molar fraction ( x i ) vs density (ρ ij ) for the mixtures MA2B and EA2B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fugacity coefficients were calculated by using the virial state equation truncated at the second term. 27 The virtual saturated vapor pressure of formaldehyde can be calculated from eq 1. The Wilson model parameters of the formaldehyde−water binary system are calculated using the experimental VL equilibrium data and Newton−Raphson iteration.…”
Section: Materials and Experimental Methodsmentioning
confidence: 99%
“…To our knowledge, no previous studies have systematically considered the VLE of all the different isomers of a single linear ester with a common second component. Extensive studies have been done into the phase behavior and mixing properties of binary mixtures of linear esters with various primary and secondary alcohols as well as with normal alkanes. These studies have adopted a systematic approach in assessing the effect of varying the alkanolic length of the ester while keeping the acidic chain length constant (or vice versa) on the phase behavior of these esters with a common second component. The choice of an n -alkane as the second component allowed these authors to attribute differences in the observed phase behavior to the dilution or concentration of polar effects due to the presence of the nonpolar alkane.…”
Section: Introductionmentioning
confidence: 99%